Analisis Kelayakan Ekonomi Implementasi Energi Surya pada Bangunan Pendidikan: Sebuah Systematic Literature Review - Ella Aprilliyah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2026)
This study aims to analyze the economic feasibility of implementing solar energy in educational buildings through a Systematic Literature Review (SLR). Data were obtained from scientific articles in the Scopus, ScienceDirect, Web of Science, and Google Scholar databases, using inclusion criteria covering the years 2015–2026 and focusing on solar power plants in educational buildings as well as economic indicators such as NPV, IRR, PP, and LCOE.The results indicate that the implementation of solar power systems in educational buildings is generally economically viable. This is evidenced by positive NPV values, IRR rates above the minimum viability threshold, and a Payback Period ranging from 6 to 16 years—which falls within the system’s economic lifespan. Key factors influencing viability include initial investment costs, electricity tariffs, solar radiation intensity, system efficiency, and government policies.In conclusion, solar power plants have great potential for application in the education sector as a solution for energy efficiency, operational cost savings, and support for sustainable energy.